Block of personal formation of the heads of the system of the Ministry of Internal Affairs of Ukraine indicators characteristics - Y. Y. Boiko-Buzyl (Law and Safety)
Emphasis is placed on the issue of professional and personal development of the heads of the Ministry of Internal Affairs of Ukraine as a psychological component of staffing the security and defense sector of Ukraine. It is stressed that the basis of professional and personal development of the heads of the system of the Ministry of Internal Affairs of Ukraine are activities and personality as basic categories reflected in the block of professional development and personal development block, and each block is identified in specific components and disclosed in relevant criteria. This article presents the second part of the study of professional and personal development of the heads of the Ministry of Internal Affairs of Ukraine, namely the psychological characteristics of the block of personal development through the following components and relevant criteria: orientation - attractiveness of professional activity, direction of professional activity; capability- leadership tools, ability for management; character - individual psychological features, the attitude of the leader to himself; reflection - the mechanism of self-analysis of the manager, the vector of personal development. The study is based on the use of a number of methods of psychological diagnosis, with the help of which during 6 months of 2020 844 people were surveyed, including 385 managers and 459 employees of bodies and departments of the Ministry of Internal Affairs of Ukraine who do not perform managerial functions. At the first stage of the study, the characteristics of indicators of professional and personal development of specialists of the system of the Ministry of Internal Affairs of Ukraine were determined. In the second stage, it was studied statistically significant differences in the characteristics of professional and personal development of managers compared to employees who do not perform managerial functions, for which the procedure of analysis of variance was used, namely one-way analysis of variance by the Fisher method. The Brown-Forsythe test was used to determine the equality of group variances. Statistical analysis of the data was performed using the ANOVA command of the SPSS program. It is proved that the indicators of the components of professional and personal formation of the management differ from similar indicators of non-leaders of the system of the Ministry of Internal Affairs of Ukraine in quality and content, in particular focus on management functions within professional activities. The obtained empirical data will contribute to the improvement of management theory and practice in the security and defense sector of Ukraine.